3‐(3, 5‐Dimethyl‐1H‐Pyrazol‐1‐yl)‐3‐Oxopropanenitrile as Precursor for Some New Mono‐Heterocyclic and Bis‐Heterocyclic Compounds. (22nd December 2015) - Metwally, Nadia H.; Abdelrazek, Fathy M.; Eldaly, Salwa M.; Metz, Peter
Abstract : 3‐(3, 5‐Dimethyl‐1 H ‐pyrazol‐1‐yl)‐3‐oxopropanenitrile1 was used as a cyanoacetylating agent for synthesis of the acetanilide derivative3 . Compound3 was utilized as a keyintermediate for the synthesis of some new mono‐chromene and di‐chromene derivatives9 and13, the dihydrazo derivatives15, and the dithiazole derivatives18 via the condensation with o ‐hydroxybenzaldehyde derivatives, the coupling with aryl diazonium salts, or the reaction with phenyl isothiocyanate in presence of KOH followed by phenacyl bromide derivatives respectively. Abstract :